Implementasi Gerakan Sekolah Menyenangkan dalam Meningkatkan Inovasi Pembelajaran Guru SD - Indah Krisnamurti; Salamah Salamah (Proceedings Series on Social Sciences & Humanities, 2022)
This study aims to analyze the improvement of teacher learning innovation in SD BOPKRI Wonosari through the application of the Fun School Movement. This research uses a descriptive qualitative approach. The time of research was carried out in the 2021/2022 academic year. The research site is at SD BOPKRI Wonosari. The subject of the study was a class teacher with a total of 6 teachers. The object of the research is the improvement of teacher learning innovation in the content of social studies lessons. Data collection techniques through observation, documentation, and interviews. Learning innovations carried out by teachers can facilitate learning, encourage active and creative students to foster students' enthusiasm for learning, achieve learning goals, and ultimately improve student learning achievements. The results of this study can be concluded that the Fun School Movement can increase the innovation of learning social studies content for teachers at SD BOPKRI Wonosari in creating a positive learning environment, comfortable and fun learning atmosphere for students, and teachers themselves.